2016
DOI: 10.1103/physrevlett.117.055301
|View full text |Cite
|
Sign up to set email alerts
|

Bose Polarons in the Strongly Interacting Regime

Abstract: When an impurity is immersed in a Bose-Einstein condensate, impurity-boson interactions are expected to dress the impurity into a quasiparticle, the Bose polaron. We superimpose an ultracold atomic gas of 87 Rb with a much lower density gas of fermionic 40 K impurities. Through the use of a Feshbach resonance and RF spectroscopy, we characterize the energy, spectral width and lifetime of the resultant polaron on both the attractive and the repulsive branches in the strongly interacting regime. The width of the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
524
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 446 publications
(542 citation statements)
references
References 38 publications
17
524
1
Order By: Relevance
“…The Efimov effect arises for resonant short-range two-body interactions in three dimensions. In previous experiments studying Bose polarons close to a Feshbach resonance it was found that these Efimov states do not strongly influence the polaron physics [7,8]. In our case the multimolecular states are not related to the Efimov effect, and dimer, trimer, etc.…”
Section: Bose Polaron Hamiltoniansmentioning
confidence: 59%
See 2 more Smart Citations
“…The Efimov effect arises for resonant short-range two-body interactions in three dimensions. In previous experiments studying Bose polarons close to a Feshbach resonance it was found that these Efimov states do not strongly influence the polaron physics [7,8]. In our case the multimolecular states are not related to the Efimov effect, and dimer, trimer, etc.…”
Section: Bose Polaron Hamiltoniansmentioning
confidence: 59%
“…So far it has been experimentally verified that the inclusion of this term is relevant for the observation of Bose polarons [7,8], where the impurity-Bose interaction can be modeled by a potential that supports only a single, weakly bound two-body molecular state. In the present work we encounter a new type of impurity problem where the impurity is dressed by large sets of molecular states that have ultra-long-range character.…”
Section: Bose Polaron Hamiltoniansmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that the interaction energy form = 0 is equivalent to the second-order perturbation due to virtual boson excitations, because f n,nt,m;u = 0 for m = 0 (see Eq. (29) with 1 r 2 u = m f ω f t |m| ) and hence only m = 0 states for boson excitations contribute to the summation in (34). This, in turn, leads to no drag effect η = 0 form = 0 via (31), as will be seen again later.…”
Section: A Mean-field Energy and Interaction Energymentioning
confidence: 66%
“…We present numerical results for the properties of a polaron in the ground and low-lying excited states, employing the parameter values that are used in the experiment for the boson-fermion mixture of 87 Rb bosons in a BEC and 40 K impurity fermions [34]:…”
Section: Numerical Results and Discussionmentioning
confidence: 99%